2021
DOI: 10.3390/ijms22147367
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Modulation of GSK-3β as a New Therapeutic Approach in Limb Girdle Muscular Dystrophy R1 Calpain 3-Related

Abstract: Limb-girdle muscular dystrophy R1 calpain 3-related (LGMDR1) is an autosomal recessive muscular dystrophy produced by mutations in the CAPN3 gene. It is a rare disease and there is no cure or treatment for the disease while the pathophysiological mechanism by which the absence of calpain 3 provokes the dystrophy in muscles is not clear. However, key proteins implicated in Wnt and mTOR signaling pathways, which regulate muscle homeostasis, showed a considerable reduction in their expression and in their phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 68 publications
(81 reference statements)
0
9
0
1
Order By: Relevance
“…Study has also revealed Tideglusib’s ability in activating PI3K/Akt signaling pathway in myotubes, hypoxic-ischemic brain injury, etc. [ 14 , 38 , 39 ]. In this study, we found that Tideglusib could promote the activation of PI3K/Akt signaling pathway in EpiSCs, thus accelerating wound healing not only in young rats but also in aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…Study has also revealed Tideglusib’s ability in activating PI3K/Akt signaling pathway in myotubes, hypoxic-ischemic brain injury, etc. [ 14 , 38 , 39 ]. In this study, we found that Tideglusib could promote the activation of PI3K/Akt signaling pathway in EpiSCs, thus accelerating wound healing not only in young rats but also in aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in mouse models of limb girdle muscular dystrophy R1 calpain 3-related (LGMDR1), in vivo administration of VP0.7 and Tideglusib restored the expression and phosphorylation of key proteins that are implicated in Wnt and mTOR signaling pathways and that are reduced in LGMDR1 patients. This suggests GSK-3β allosteric modulation could be a possible therapeutic strategy for this disease [ 98 ]. In addition, administration of VP0.7 and TDZD-8 in experimental mouse models of AE reduced pathology severity [ 99 ], hinting at GSK-3β as a feasible target for new therapeutic interventions for AE.…”
Section: Gsk-3β Inhibitionmentioning
confidence: 99%
“…Schlüsselproteine, die die Muskelhomöostase regulieren, zeigten eine beträchtliche Verringerung ihrer Expression und ihrer Phosphorylierung in Muskeln von LGMD2A/R1-Patienten. Die Verabreichung von Tideglusib und VP0.7, beides ATP-nicht-kompetitive Inhibitoren der Glykogensynthase Kinase 3β, führten in LGMD2A/R1 Zellen zur Wiederherstellung der Expression und Phosphorylierung von Proteinen, die an den Wnt-und mTOR-Signalwegen beteiligt sind, so dass sich hier neue therapeutische Optionen ergeben [14]. [15,16].…”
Section: Inhibitoren Der Glykogensynthase Kinase 3βunclassified